2022
DOI: 10.3390/ijerph19159479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Classroom Physical Activity Breaks on Children’s Academic Performance, Cognition, Health Behaviours and Health Outcomes: A Systematic Review and Meta-Analysis of Randomised Controlled Trials

Abstract: In-Classroom physical activity breaks (IcPAB) are a promising way to promote children’s health behaviors, while contributing to the development of their academic and cognitive ability and health outcomes. Yet the effect of the activity breaks, which are exclusive to classroom settings, are still mixed and unclear. Hence, this review was conducted to identify the characteristics and the effects of IcPAB among primary school children. The review protocol was registered on PROSPERO (CRD42021234192). Following the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…The heterogeneity was assessed using the I 2 , with I 2 values of 25%, 50%, and 75% indicating low, medium, and high heterogeneity, respectively [24]. The publication bias was evaluated using funnel plots and Egger's regression tests [25,26]. The subgroup analyses were implemented on study quality and demographics in case the number of included samples is no less than 10 [22,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity was assessed using the I 2 , with I 2 values of 25%, 50%, and 75% indicating low, medium, and high heterogeneity, respectively [24]. The publication bias was evaluated using funnel plots and Egger's regression tests [25,26]. The subgroup analyses were implemented on study quality and demographics in case the number of included samples is no less than 10 [22,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…(1) Not enough studies focused on introducing integrated PA into academic content through classroom-based interventions ( 37–40 ). (2) Most of those studies are introduced for populations from high-income Western countries ( 37 , 39 , 41 ) such as the USA, Australia, the Netherlands and Switzerland. The intervention effects based on gender are understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention effects based on gender are understudied. (3) Different durations were used in previous IcPAB initiatives, ranging from 10 min to 4,800 min ( 37 ), even though teachers prefer activity breaks that will take no more than 5 minutes ( 37 ), and the effectiveness of five-minute IcPAB interventions are understudied ( 37 ). (4) Previous studies demonstrated average methodological quality, with concerns around the randomization procedure, handling of missing data, outcome and process evaluation ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have shown that dietary and PA interventions can improve FV intake and MVPA in children [ 13 , 14 ], and in particular that multifaceted interventions using both diet and sports participation (SP) are more effective than diet or SP interventions alone in improving children’s health [ 15 , 16 , 17 ], there is still a lack of sustainable and structured intervention programs. Most of the current diet and SP program for children in China have been designed with the specific goal of improving obesity, neglecting the development of lifestyle-related interventions such as improving children’s eating and PA behavior [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%